Impact of Bariatric Surgery on Carotid Artery Inflammation and the Metabolic Activity in Different Adipose Tissues. Issue 20 (May 2015) - Bucerius, Jan; Vijgen, Guy H.E.J.; Brans, Boudewijn; Bouvy, Nicole D.; Bauwens, Matthias; Rudd, James H.F.; Havekes, Bas; Fayad, Zahi A.; van Marken Lichtenbelt, Wouter D.; Mottaghy, Felix M.; Pineiro., Daniel
<x xml:space="preserve">Abstract</x> Abstract In this study, we unravel a molecular imaging marker correlated with the known reduction of cardiovascular events (most commonly related to vulnerable plaques) in morbidly obese patients after bariatric surgery (BaS). We prospectively imaged 10 morbidly obese subjects with 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography before and 1 year after BaS. 18F-FDG uptake—which is enhanced in inflamed, atherosclerotic vessels and in metabolically active adipose tissues—was quantified in the carotids, pericardial adipose tissue (PAT), visceral adipose tissue (VAT), as well as brown adipose tissue (BAT). The degree of carotid inflammation was compared to lean and overweight controls. Carotid inflammation significantly declined leading to an 18F-FDG uptake comparable to the 2 control groups. Metabolic activity significantly decreased in PAT and VAT and increased in BAT. BaS leads to a normalization of carotid artery inflammation and a beneficial impact on the metabolic activity in PAT, VAT, and BAT that is related to the metabolic syndrome observed in this patient group.